Kebijakan Pembangunan Pariwisata Berkelanjutan Di Desa Pulau Maringkik Kabupaten Lombok Timur - RR. Cahyowati; Galang Asmara; Gatot Dwi Hendro Wibowo (Unram Journal of Community Service, 2022)
Maringkik Island Village is the outermost island of Lombok Island, located in the middle of the sea, in the Keruak District, East Lombok Regency with an area of 6 ha, consisting of a population of 2343 people. This paper aims to analyze sustainable tourism development policies, the obstacles faced, and solutions. The method used in this activity was carried out using a participatory method by conducting focus group discussions (FGD). In conclusion, Pulau Maringkik Village is the only Archipelagic Tourism Village in East Lombok which was determined based on East Lombok Regent Decree No 188.45/QB3/Par/2021, the obstacles faced, namely population density, the allocation for tourism development at the village level is only 1,67%. the people are not yet open to tourists, especially foreign tourists, public awareness of the potential for tourism in their area has not been built, limited supply of clean water, guidance, and assistance has not been carried out by the Regional Government of East Lombok Regency, waste management has not been carried out, facilities and infrastructure supporting tourism are still limited, Solution, The East Lombok Regency Government needs to carry out continuous guidance and assistance in order to build sustainable tourism, provide counseling about tourism potential in Maringkik Island Village so that people understand the benefits of developing tourism in their area, structuring clean water sources, waste handling, provision of facilities and tourism infrastructure can cooperate with, East Lombok Regency Government, Tourism Office, and Travel Bureau